Calculation on the radiation noise of ceramic ball bearings based on dynamic model considering nonlinear contact stiffness and damping. (4th August 2020) - Wu, Yuhou; Yan, Haipeng; Li, Songhua; Zhang, Ke; Zhang, Lixiu
Abstract: Radiation noise (RN) is an important parameter for representing the characteristics of a bearing. By simplifying a ball bearing as a mass–spring–damping system, the differential equations for the vibration of an angular contact ceramic ball bearing (ACCBB) are established from the view of energy conservation considering nonlinear contact stiffness and damping. Then, the RN model of the bearing is constructed by Helmholtz's acoustic theory. The bearing noise is calculated using the proposed model, and the corresponding experiments are performed to confirm the model precision. The bearing noise consists of the noise at the characteristic frequency of each component; the rotational frequency is the primary contributor to the bearing noise. The radiation noise first increases with increasing rotational speed and the sound pressure level (SPL) has a high peak value at a critical speed of 28, 000 r·min −1 . Then, the noise decreases with increasing rotational speed. The directivity of sound field is discussed at different rotational speed. With increasing the rotational speed, the directivity level (DL) increases and the directivity angle (DA) skews towards the rotation direction. The research provides a theoretical basis to analyze the RN generated by ACCBBs at different rotational speeds. Graphical abstract: Image 1 Highlights: A novel method for calculating the bearing noise is proposed based on dynamic response. Radiation noise of an angular contact ceramic ball bearing is investigated. Total SPL and acoustic spectrum are analyzed by calculated and experimental results. The effect of the characteristic frequency on the bearing noise is examined. The directivity of sound field for an angular contact ball bearing is discussed.